2013
DOI: 10.1002/jcb.24590
|View full text |Cite
|
Sign up to set email alerts
|

The protein ERp57 contributes to EGF receptor signaling and internalization in MDA-MB-468 breast cancer cells

Abstract: The disulfide isomerase ERp57 is a soluble protein mainly located in the endoplasmic reticulum, where it acts in the quality control of newly synthesized glycoproteins, in association with calreticulin and calnexin. It has been also detected in other cell compartments, such as the cytosol, the plasma membrane and the nucleus. In these locations it is implicated in various processes, participating in the rapid response to calcitriol, modulating the activity of STAT3 and being requested for the pre-apoptotic exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
(50 reference statements)
0
28
0
2
Order By: Relevance
“…Downregulation of the expression of PDIA3 is associated with a poor prognosis in early-stage cervical cancer (21). In addition, PDIA3 was found to contribute to epidermal growth factor receptor signaling and internalization in breast cancer cells (22). A previous study demonstrated that PDIA3 is involved in paclitaxel resistance in ovarian cancer by interacting with class III β-tubulin (23).…”
Section: Discussionmentioning
confidence: 98%
“…Downregulation of the expression of PDIA3 is associated with a poor prognosis in early-stage cervical cancer (21). In addition, PDIA3 was found to contribute to epidermal growth factor receptor signaling and internalization in breast cancer cells (22). A previous study demonstrated that PDIA3 is involved in paclitaxel resistance in ovarian cancer by interacting with class III β-tubulin (23).…”
Section: Discussionmentioning
confidence: 98%
“…PDIA3 is involved in cell proliferation and stabilizing receptors on the cell membrane (19,20) and intracellular signaling molecules, including signal transducer and activator of transcription 3 (21) and mechanistic target of rapamycin (22). In hepatocellular carcinoma, high expression of PDIA3 was associated with high proliferative activity and low apoptotic cell death, whereas low expression was associated low proliferative activity and high apoptotic cell death (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been linked to DNA repair as a member of the damage recognition complex and as a potential regulator that binds to genes with recognized repair functions (Chichiarelli et al, 2007). Several studies have linked PDIs to different types of cancer, including gastric (Leys et al, 2007), prostate (Pressinotti et al, 2009), esophageal (Ayshamgul et al, 2011), cervical (De Marco et al, 2012;Chung et al, 2013), salivary gland (Müller et al, 2013), bone metastasis (Santana-Codina et al, 2013), and breast (Lee et al, 2012;Gaucci et al, 2013) cancers. Another gene in this superfamily, PDIA6, also encodes a product that exhibits chaperone activity by inhibiting misformed protein aggregation.…”
Section: Introductionmentioning
confidence: 99%